2013
DOI: 10.3109/09638288.2013.782355
|View full text |Cite
|
Sign up to set email alerts
|

Role of physical activity in the occurrence of falls and fall-related injuries in community-dwelling adults over 50 years old

Abstract: Purpose: This study examined the effect of the type, level and amount of physical activity in falls and fall-related injuries. Method: Participants were 506 community-dwelling adults aged 450 years (390 women: 67.7 AE 6.8 years and 116 men: 69.6 AE 6.6 years). Falls, fall-related injuries (slight and severe), and physical activity (type, level and energy expenditure) were evaluated by questionnaires. Confounders included co-morbidities, fear of falling, environmental hazards and physical fitness. Results: Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 41 publications
0
56
3
2
Order By: Relevance
“…Results for the sexes were opposite; men with low mobility had an increased falls risk, whereas women who had low mobility had a decreased risk. Both low and high mobility can lead to an increase in falls (Delbaere et al, 2010;Pereira et al, 2014). A moderate amount of physical activity can aid in maintaining balance and muscle strength (Hadjistavropoulos et al, 2011), however a high level of physical activity can result in an increased risk of falls through increased exposure to risky activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Results for the sexes were opposite; men with low mobility had an increased falls risk, whereas women who had low mobility had a decreased risk. Both low and high mobility can lead to an increase in falls (Delbaere et al, 2010;Pereira et al, 2014). A moderate amount of physical activity can aid in maintaining balance and muscle strength (Hadjistavropoulos et al, 2011), however a high level of physical activity can result in an increased risk of falls through increased exposure to risky activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple benefits of regular physical activity on morbidity and mortality are well known . Elderly persons who are physically active are less likely to have falls and fall‐related severe injuries, such as fractures , but the data on the effect of physical activity on the risk of bleeding are conflicting. While studies showed that physical activity is associated with a lower risk of severe gastrointestinal hemorrhage and hemorrhagic stroke , other studies demonstrated that vigorous physical activity is related to an increased risk of subarachnoid hemorrhage in adults and bleeding events in children with hemophilia .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we assessed the association between physical activity and bleeding in a prospective, multicenter cohort of elderly patients receiving anticoagulants for venous thromboembolism (VTE). Because elderly persons who are physically active are less likely to fall , we hypothesized that a higher level of physical activity will be associated with a lower risk of bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, long-term inactivity may predispose an individual to develop a host of medical issues, including obesity and diabetes [23]. Previous research has indicated that increasing one's level of physical activity decreases fall risk and safeguards against injury [24]. Additionally, prolonged engagement in an inactive lifestyle may put individuals at a higher risk for falling when they do physically exert themselves because of the muscle deconditioning and weakness associated with prolonged sedentariness [7].…”
Section: Physical Activity Levelmentioning
confidence: 99%